RELAKSASI BENSON MEMPENGARUHI ASPEK PSIKOLOGIS PADA KUALITAS HIDUP PASIEN PASCA KEMOTERAPI CA MAMAE - Prajayanti, Eska Dwi; Sari, Irma Mustika (LPPM STIKES MUHAMMADIYAH GOMBONG, 2017)
Patients ca mamae who through the chemotherapy process will experience a decrease in quality of life. Among other things is the decline in the psychological aspects. These psychological aspects include despair, negative thoughts, anxiety, and decreased self-esteem. This study aims to determine the effect of Benson relaxation on psychological aspects of the quality of life of patients with ca mamae after chemotherapy. This research method is design Quasi studies pre-posttest control an experimental group design. The number of samples in this study were 22 respondents using purposive sampling technique. The sample was divided into treatment group and control group as one of the respondents by handling in accordance with hospital standard without Benson relaxation. Result there was an effect of Benson relaxation related to psychological aspects on quality of life of Ca mamae (sign 2- tailed <0.05). The conclusion that benson relaxation is one of the alternative relaxation techniques that can be utilized to improve the psychological domain of ca mamae